2021
DOI: 10.1109/access.2021.3061743
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of a Flywheel Energy Storage Matrix System: An External Model Approach

Abstract: This paper studies the coordination of a heterogenous flywheel energy storage matrix system aiming at simultaneous reference power tracking and state-of-energy balancing. It is first revealed that this problem is solvable if and only if the state-of-energy of all the flywheel systems synchronize to a common time-varying manifold governed by a nonautonomous dynamic system. Next, by treating this nonautonomous dynamic system as an external model, the coordination problem can be decoupled into two separate proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…[7][8][9] Many authors have described various kinds of ESSs such as battery ESS (BESS), 10 compressed air ESS (CAESS), 11 supercapacitor ESS (SCESS), 12 thermal ESS (TESS), 13 superconducting magnetic ESS (SMESS), 14,15 hydrogen ESS (HESS), 16 pumped hydro ESS (PHESS), 17 and flywheel ESS (FESS). [18][19][20] A comparative study of different ESSs and their advantages and disadvantages are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Many authors have described various kinds of ESSs such as battery ESS (BESS), 10 compressed air ESS (CAESS), 11 supercapacitor ESS (SCESS), 12 thermal ESS (TESS), 13 superconducting magnetic ESS (SMESS), 14,15 hydrogen ESS (HESS), 16 pumped hydro ESS (PHESS), 17 and flywheel ESS (FESS). [18][19][20] A comparative study of different ESSs and their advantages and disadvantages are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, ESSs plays a significant role in the electrical network by storing electrical energy, converting it into various forms, and supplying it whenever necessary, in the form of electricity 7‐9 . Many authors have described various kinds of ESSs such as battery ESS (BESS), 10 compressed air ESS (CAESS), 11 supercapacitor ESS (SCESS), 12 thermal ESS (TESS), 13 superconducting magnetic ESS (SMESS), 14,15 hydrogen ESS (HESS), 16 pumped hydro ESS (PHESS), 17 and flywheel ESS (FESS) 18‐20 . A comparative study of different ESSs and their advantages and disadvantages are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…A novel dual-channel bearingless switched reluctance motor (DCBSRM) is proposed in this paper, which exhibits the following advantages: (1) The coupling between electromagnetic torque and radial force can be weakened due to the dual-phase-conduction strategy; (2) The radial load capacity can be enhanced and the radial suspension performance can be improved for the widened rotor poles; (3) The fault tolerance can be raised by dual-channel operation; (4) The integration of motor is raised. The advantages mentioned above are analyzed and verified in the succeeding sections.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Zhang et al (2022) does not consider the specific dynamics of the flywheel systems. In contrast, Liu et al (2021) studied the dual objective coordination of FESMS taking into consideration the detailed flywheel dynamics, where it is revealed that the dual control objective can be achieved if and only if the SOE of each flywheel converges to a common SOE generator, which was shown to be a nonautonomous dynamic system with the reference command for the entire FESMS as the external input. By explicitly implementing this nonautonomous dynamic system as an external model, the coordination problem for the FESMS was solved in Liu et al (2021) by a distributed control approach.…”
mentioning
confidence: 99%
“…In contrast, Liu et al (2021) studied the dual objective coordination of FESMS taking into consideration the detailed flywheel dynamics, where it is revealed that the dual control objective can be achieved if and only if the SOE of each flywheel converges to a common SOE generator, which was shown to be a nonautonomous dynamic system with the reference command for the entire FESMS as the external input. By explicitly implementing this nonautonomous dynamic system as an external model, the coordination problem for the FESMS was solved in Liu et al (2021) by a distributed control approach. However, a drawback of this control approach lies in that the implementation of the external model depends on the system parameters of all the flywheel systems, which are global system information.…”
mentioning
confidence: 99%